Sphingosine-1 Phosphate: A New Modulator of Immune Plasticity in the Tumor Microenvironment - Rodriguez, Yamila I.; Campos, Ludmila E.; Castro, Melina G.; Aladhami, Ahmed; Oskeritzian, Carole A.; Alvarez, Sergio E. (Frontiers in Oncology, 2016)
In the last 15 years, increasing evidences demonstrate a strong link between sphingosine-1-phosphate (S1P) and both normal physiology and progression of different diseases, including cancer and inflammation. Indeed, numerous studies show that tissue levels of this sphingolipid metabolite are augmented in many cancers, affecting survival, proliferation, angiogenesis, and metastatic spread. Recent insights into the possible role of S1P as a therapeutic target has attracted enormous attention and opened new opportunities in this evolving field. In this review, we will focus on the role of S1P in cancer, with particular emphasis in new developments that highlight the many functions of this sphingolipid in the tumor microenvironment. We will discuss how S1P modulates phenotypic plasticity of macrophages and mast cells, tumor-induced immune evasion, differentiation and survival of immune cells in the tumor milieu, interaction between cancer and stromal cells, and hypoxic response.